2018
DOI: 10.1016/j.jhazmat.2018.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Linking initial soil bacterial diversity and polycyclic aromatic hydrocarbons (PAHs) degradation potential

Abstract: The aim of this study was to understand the role of indigenous soil microbial communities on the biodegradation of polycyclic aromatic hydrocarbons (PAHs) and to determine whether PAHs degradation potential in soils may be evaluated by analysis of bacterial diversity and potential metabolisms using a metagenomics approach. Five different soils were artificially contaminated with seven selected PAHs and the most abundant bacterial taxa were assessed by sequencing the 16S rRNA gene, and linking them to PAH biode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…OTUs in the COV samples were available in the reference SilvaMod 123 database (for which reference pathways are available in the Tax4Fun package) than in CH samples, which suggested that the OTUs that inhabited the more contaminated sites are more ubiquitous in nature and thus well characterised with their pathways available. The gene content for each OTU in each sample was inferred from the closest sequenced genome using the Tax4Fun package and we investigated particular pathways from the KEGG database linked to contaminant degradation 4 and related metabolic pathways. Out of the 12 tested pathways, seven presented signicantly different average relative abundance between COV and CH.…”
Section: Bacterial Diversity In Ch and Cov Soilsmentioning
confidence: 99%
See 2 more Smart Citations
“…OTUs in the COV samples were available in the reference SilvaMod 123 database (for which reference pathways are available in the Tax4Fun package) than in CH samples, which suggested that the OTUs that inhabited the more contaminated sites are more ubiquitous in nature and thus well characterised with their pathways available. The gene content for each OTU in each sample was inferred from the closest sequenced genome using the Tax4Fun package and we investigated particular pathways from the KEGG database linked to contaminant degradation 4 and related metabolic pathways. Out of the 12 tested pathways, seven presented signicantly different average relative abundance between COV and CH.…”
Section: Bacterial Diversity In Ch and Cov Soilsmentioning
confidence: 99%
“…Specically, metataxogenomic and metagenomic approaches have demonstrated that contamination induces a reduction in species richness and enriches the population with species that are adapted to hydrocarbon degradation. 3 Consequently, initial microbial ecology could also be linked to the potential for PAH degradation, 4 demonstrating that microbial ecology carries meaningful information on the potential for bioremediation in soil. However, without high resolution information on the contamination prole, notably the presence of other contaminants, this information might not be sufficient for the design of an efficient site-specic bioremediation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar is the product of limited oxygen pyrolysis of biomass and is used in agriculture as a soil improver, compost additive and livestock feed supplement [1][2][3][4].Some studies have investigated whether biochar not only provides space for soil microorganisms with pore structures but also provides nutrients to soil microorganisms to enhance their growth, and these nutrients are adsorbed on the biochar [5,6]. In this way, biochar will positively affect soil microbes, thereby accelerating the biodegradation of organic contaminants in soil.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of soil amendment, the use of biochar with functional microorganisms to treat contaminated soil will not only affect organic contaminant degradation and catabolic pathways but also affect the global biogeochemical cycles of nutrient elements [1,16]. Studies have found that biochar produced via pyrolysis of biomass wastes can enhance and supply long-term soil organic carbon storage [17,18].…”
Section: Introductionmentioning
confidence: 99%